Penggunaan Model Pembelajaran Talking Chips Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV SD Negeri 0105 Sibuhuan Julu - Lailan Aprina Siregar; Irma Sari Daulay; Amsal Mahbubi Hasibuan (CV. Aksara Global, 2023)
This research aims (1) to determine student learning outcomes in the science subject style material in class IV of SD Negeri 0105 Sibuhuan Julu. (2) To determine the increase in student learning outcomes by using the talking chips learning model in the science subject style material in class IV of SD Negeri 0105 Sibuhuan Julu. The type of research used is classroom action research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. The data sources in this research were divided into two, namely (1) primary data from class IV participants at SD Negeri 0105 Sibuhuan Julu, (2) secondary data namely class IV teachers at SD Negeri 0105 Sibuhuan Julu. Data collection techniques in this research were obtained through interviews, observation, written tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the research results, it can be concluded that: (1) Student learning outcomes before using the talking chips learning model in the science subject style material in class IV of SD Negeri 0105 Sibuhuan Julu obtained Minimum Completeness Criteria (KKM) data for 8 students with a percentage of 30 .67% and there were 19 students who had not reached the KKM with a percentage of 73.33%. (2) Student learning outcomes before using the talking chips learning model in the science subject style material in class IV of SD Negeri 0105 Sibuhuan Julu, Barumun District, Padang Lawas Regency, obtained action data for cycle I which had reached the Minimum Completeness Criteria (KKM) for 16 students. with a percentage of 53.33% and those who have not yet reached the KKM are 14 students with a percentage of 46.67%.. Cycle II actions that have reached the Minimum Completion Criteria (KKM) are 23 students with a percentage of 90% and there are 3 who have not reached the KKM students with a percentage of 10%. It can be concluded that the talking chips learning model can improve the learning outcomes of fourth grade students at SD Negeri 0105 Sibuhuan Julu.